The Tourist Preference in Choosing Accommodation in Bali - Devana, Skolastika Marcia; Arismayanti, Ni Ketut; Ariana, I Nyoman Jamin (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 3 (2018): Vol.2,No.3,2018, 2019)
The research was conducted in Bali. The background of this research is necessity to know the preference of tourist about accommodation while they on vacation in Bali. The type of data were used in the qualitative and quantitative data, while data sources were used primary data and secondary data. Retrieval of data collection techniques were used observation, interviews, questionnaire, documentation and literature study. Data analysis technique were used descriptive statistics and conjoint analysis, with nine variables (location, price, past experiences, recommendation, reputation, loyalty program points/ membership, online reviews, facilities or services and green program). The determination technique of respondents were accidental sampling and slovin formula with 100 respondents. The results of this research is the most important variabel according the tourist in choosing accommodation in Bali is the location. Also, the results of the tourist preference in choosing accommodation in Bali are the accommodation located near foreshore, rating accommodation is above 8, the accommodation price below than Rp 500.000, the accommodation have green program, accommodation have a loyalty or membership program, not chain property, the accommodation recommended by others, the accommodation has never been occupied before and the accommodation have complete facilities. Suggestions in this study is the accommodation industry should pay more attention to attribute location, online review and price. Second, the industry expected to keep and maintain online review and e-commerce. Third, the next researcher can combine between conjoint and cluster analysis to maximise the result from different market segments. Furthermore, it is suggested to further research that have the same focus dan locus for disseminationg a questionnaire at the airport. The last suggestion, sugeested to the government that it may review and reset the accommodation policy especially the particular types of accommodation.  Keywords : Preference, Tourist, Accomodation, Bali